Gottesdienstliches digitales Neuland in Zeiten der Pandemie: ein Erfahrungsbericht in theologischer Absicht - Springhart, Heike (Evangelische Theologie, 2021)
This paper offers reflections of broadcasted church services by describing and analyzing concrete experiences with online services, which are produced professionally by using the chances and means of filming. From that vantage point general theological issues in the COVID-19 era are addressed, in particular those that are related to the transformation in celebrating services. The importance of bodily resonances and the importance of synchronicity are addressed as well as the ecclesiological issue about the various publics and the various ways in which the church speaks. The various aspects are connected by the conviction that the practical and ethical necessities in times of COVID-19 raise general theological questions beyond the pandemic.